PENINGKATAN KEMANDIRIAN BELAJAR SISWA MELALUI LAYANAN BIMBINGAN KELOMPOK - Elfira, Ninil (Konselor, 2013)
During the learning process, students need to be competence. Group guidance can be used to improve the independency of the students. An experimental pre post-test control group design was utilized to test whether group guidance can better improve theindependency of student’s learning. Two purposive sample classes of student were selected from SMA N 1 and SMA N 2 Sungai Tarab. The findings of this study were: (1) there is a significant difference between pre-test and posttest score of the experimental group and (2) significant difference between the experimental group on the students' independence score with self control group.